Influence of Microbiological Complexes on the Fatty Acid Composition of Corn Seedlings - Melnychuk, T.M.; Midyk, S.V.; Biliavska, L.O.; Makarchuk, O.S.; Zhemoida, V.L.; Machuskyy, O.V.; Vishovan, Yu.Yu.; Loboda, M.I.; Skrotsky, S.O.; Samkova, O.P.; Korniyenko, V.I.; Spriazhka, R.O.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
Microorganisms in combination with metabolic complexes have a positive effect on the growth and development of plants, forming their protective, adaptogenic, and anti-stress properties. The aim of the study was to research the fatty acid composition of lipids in the microbial bioformulations Sporazyn and Ecophosphoryn, as well as in corn seedlings, under the influence of seed inoculation with microbiological complexes. Methods. Seeds and seedlings of corn of the interlineage hybrid of lines 1-Ak026 and 2-Ak033 were treated with Microbiological Complex 1 (MC1), includes bioformulations Sporazyn, Averkom, Phytovit, and Microbiological Complex 2 (MC2) based on Ecophosphoryn. Lipids from the analyzed samples were extracted by the Folch method. Hydrolysis and methylation of fatty acids from lipids extracted from corn seedlings were conducted in accordance with DSTU ISO 5509-2002, followed by analysis using the GC method. Results. The content of saturated and unsaturated fatty acids in the lipid complex of Sporazyn and Ecophosphoryn was found to be at a similar level. Ecophosphoryn differed from Sporazyn in the increased content of monounsaturated and omega-9 fatty acids. The lipid complex of Sporazyn had a higher content of polyunsaturated and omega-6 fatty acids than Ecophosphoryn. The impact of microbiological complexes on the sowing properties of corn seeds was identified. The application of MC1 (Sporazyn, Averkom, Phytovit) enhanced corn seed germination and germination energy by 6%. Under the influence of MC2 (Ecophosphoryn, Averkom, and Phytovit), germination rates and germination energy  increased by 8.3 and 6.4%, respectively, compared to uninoculated seeds. The Alysinas of the lipid complex in corn seedlings identified 21 fatty acids, with their quantitative composition varying based on the applied microbiological complex. Conclusions. Under the influence of MK1, the content of behenic, caproic, and cis-13,16-docosadienoic acids increased by 2.1-fold, 7.8-fold, and 8.3-fold, respectively. In contrast, MC2 resulted in a decrease in their content by 1.4, 1.5, and 1.7-fold. Similar trends were observed in lignoceric, myristic, and palmitic acids. Seed treatment with MC1 enabled the detection of caprylic, capric, and lauric acids, which were absent in both the control and MC2-treated groups. Inoculation with both microbiological complexes led to an increase in linolenic (by 0.04–0.33%) and heptadecenoic (by 0.01%) acid content, while reductions were noted in oleic (by 0.43–9.76%) and arachidonic (0.02–0.05%) acids.